Mental Insanity Assessment of Pedophilia: The Importance of the Trans-Disciplinary Approach. Reflections on Two Cases - Scarpazza, Cristina; Pennati, Ambrogio; Sartori, Giuseppe (Frontiers in Neuroscience, 2018)
A 60 plus-year-old male was charged with paedophilia for forcing a child to touch him inappropriately near a primary school fence. In another case, a 70 plus-year-old male was charged with paedophilia for intimately touching a boy in a cinema. What led them to manifest this socially-inappropriate and legally-relevant behaviour? Is there an explanation for the sexually-related behavioural changes emerging late in life of these two men? Indeed, a common point exists between the two men: both were found to suffer from highly-disabling neurological conditions, known to have a potential effect on social behaviour. Specifically, a large right frontoparietal meningioma was found to have important influence on the first man’s cognition and control inhibition, whereas frontotemporal dementia prevented the second man from understanding the moral disvalue of his sexually-inappropriate behaviour and controlling his sexual impulses. In the current presentation, particular emphasis is placed on the logical reasoning supporting the conclusions that both the paedophiles should be considered not guilty by reason of insanity. Furthermore, experimental methods have been used to explore both cases, which rely on the existence of cognitive models for the phenomena under study, the integration of insights offered by different disciplines and the application of a variety of tools and approaches that follow the “convergence of evidence” principle, which could be safely used in court to support a mental insanity claim. Here, we describe how the use of the experimental method could become useful to reduce the uncertainty in mental insanity assessments. The use of a transdisciplinary,